Burnout Syndrome Among Nursing Staff: Performing Data Analysis using the SPSS Statistic - Lafraxo, Mohammed Amine; Ouadoud, Mohammed; El Madhi, Youssef; Soulaymani, Abdelmajid (International Journal of Online and Biomedical Engineering (iJOE), 2021)
This study aimed to evaluate the prevalence of burnout among nurses, to determine the socio-demographic characteristics associated with burnout, and to assess the influence of the practice of physical activities on burnout. This is an observational study of a cross-sectional type. A self-administered survey was used to determine the socio-demographic and professional characteristics. The Copenhagen Burnout Inventory to evaluate burnout and the Ricci-Gagnon questionnaire to assess the level of physical activity and sports practice. In total, 16.7% of the participating nurses displayed a high level of general burnout (63.3% medium, 20% low), and 23% displayed a high level of patient-related burnout (34% medium, 43% low). Physical activity had no protective effect against burnout, as 87% of participants were physically active. This research result confirmed what exists in other scientific publications; the prevalence of burnout is a reality in the health professions. It is necessary to think of setting up accompaniments to sensitize nurses for primary prevention against burnout.